Bank regulation in the selected Sub-Saharan African countries: Dynamics and trends - Retselisitsoe I. Thamae; Nicholas M. Odhiambo; John M. Khumalo (Journal of Central Banking Theory and Practice, 2023)
This paper discusses the dynamics of bank regulation in the Sub-Saharan African (SSA) region during the period before the 1990s and post 1990s and describes the trends in bank regulatory measures between 1995 and 2017 using the updated databases of the World Bank's Bank Regulation and Supervision Surveys, Before the 1990s, bank regulation in the majority of SSA countries was inadequate and that led to multiple occurrences of banking crises, As a result, many countries introduced the financial sector reforms from the late 1980s that included major adjustments in the banking regulatory and supervisory frameworks, In both low-income and middle-income SSA economies, bank regulatory environment became more stringent over time, driven by increased restrictions on bank entry barriers and ownership structure, as well as the introduction of macroprudential policies in the case of the former, while in the case of the latter, it was influenced by more restrictions on bank ownership structure and capital regulation requirements, as well as the adoption of macroprudential policies, Overall, the bank regulatory environment was slightly more stringent in middle-income than in low-income SSA countries over the period under review.
Keywords: E58; G28; 330; Bank regulation; dynamics; trends; Sub-Saharan Africa